Catastrophic Health Expenditure Associated With Frailty in Community-Dwelling Chinese Older Adults: A Prospective Cohort Analysis - Fan, Lijun; Hou, Xiang-Yu; Liu, Yingyan; Chen, Sunan; Wang, Qian; Du, Wei (Frontiers in Public Health, 2021)
Background: Catastrophic health expenditure (CHE) represents a key indicator for excessive financial burden due to out-of-pocket healthcare costs, which could push the household into poverty and is highly pronounced in households with members at advanced age. Previous studies have been devoted to understanding the determinants for CHE, yet little evidence exists on its association with frailty, an important geriatric syndrome attracting growing recognition. We thus aim to examine the relationship between frailty and CHE, and to explore whether this effect is moderated by socioeconomic-related factors. Methods: A total of 3,277 older adults were drawn from two waves (2011 and 2013) of the China Health and Retirement Longitudinal Study (CHARLS). CHE was defined when out-of-pocket healthcare expenditure exceeded a specific proportion of household’s capacity to pay. Frailty was measured following the Fried Phenotype (FP) scale. Mixed-effects logistic regression models were employed to assess the longitudinal relationship between frailty and CHE, and stratification analyses were conducted to explore the moderation effect. Results: The incidence of CHE among Chinese community-dwelling older adults was 21.76% in 2011 and increased to 26.46% in 2013. Compared with non-frail individuals, those pre-frail or frail adults were associated with higher odds for CHE after controlling for age, gender, residence, education, marriage, income, health insurance, smoking, drinking and comorbidity (pre-frail: OR=1.32, 95%CI=1.14-1.52; frail: OR=1.67, 95%CI=1.13-2.47). Three frailty components including weakness, exhaustion and shrinking contributed to significantly increased likelihood of CHE (all p<0.05), while the other two components including slowness and inactivity showed non-significant effect (all p>0.05). Similar effects from frailty on CHE were observed across socioeconomic-related subgroups differentiated by gender, residence, education, household income, and social health insurance. Conclusions: Frailty is a significant predictor for catastrophic health expenditure in China. Developing and implementing cost-effective strategies for prevention and management of frailty is imperative to protect households from financial catastrophe.